Seasonal soil VOC exchange rates in a Mediterranean holm oak forest and their responses to drought conditions - ASENSIO, D.; Penuelas, J.; Ogaya, R.; Llusia, J. (Atmospheric Environment, 2007)
Available information on soil volatile organic compound (VOC) exchange, emissions and uptake, is very scarce. We here describe the amounts and seasonality of soil VOC exchange during a year in a natural Mediterranean holm oak forest growing in Southern Catalonia. We investigated changes in soil VOC dynamics in drought conditions by decreasing the soil moisture to 30% of ambient conditions by artiﬁcially excluding rainfall and water runoff, and predicted the response of VOC exchange to the drought forecasted in the Mediterranean region for the next decades by GCM and ecophysiological models. The annual average of the total (detected) soil VOC and total monoterpene exchange rates were 3.273.2 and 0.470.3 mg m 2 h 1 , respectively, in control plots. These values represent 0.003% of the total C emitted by soil at the study site as CO2 whereas the annual mean of soil monoterpene exchange represents 0.0004% of total C. Total soil VOC exchange rates in control plots showed seasonal variations following changes in soil moisture and phenology. Maximum values were found in spring (1778 mg m 2 h 1 ). Although there was no signiﬁcant global effect of drought treatment on the total soil VOC exchange rates, annual average of total VOC exchange rates in drought plots resulted in an uptake rate (0.571.8 mg m 2 h 1 ) instead of positive net emission rates. Larger soil VOC and monoterpene exchanges were measured in drought plots than in control plots in summer, which might be mostly attributable to autotrophic (roots) metabolism. The results show that the diversity and magnitude of monoterpene and VOC soil emissions are low compared with plant emissions, that they are driven by soil moisture, that they represent a very small part of the soil-released carbon and that they may be strongly reduced or even reversed into net uptakes by the predicted decreases of soil water availability in the next decades. In all cases, it seems that VOC ﬂuxes in soil might have greater impact on soil ecology than on atmospheric chemistry
Keywords: climate change; Drought; Mediterranean holm oak forest; Monoterpenes; Soil CO2 flux; Soil VOC exchange